Caries dental y estado nutricional en niños de 3 a 5 años de la I.E.C.J nº 168 “Gotitas del Saber” Santa Clara de Nanay, 2023 - Ramirez Muñoz, Diego José (2023)
OBJECTIVE: The present study sought to determine the association between dental caries and nutritional status in children aged 3 to 5 years from the I.E.C.J No. 168 “Gotitas del Saber” Santa Clara de Nanay, 2023. METHOD: A quantitative investigation was developed. Non-experimental, transversal and correlational design. Made up of 163 minors, criteria established by the National Center for Food and Nutrition (CENAN) were used to determine nutritional status, in relation to weight for height, weight for age, height for age, in addition to the ceo-d index established by the World Health Organization to determine the level of dental caries. RESULTS: In relation to dental caries, of 163 (100%) minors evaluated, the sample represents approximate percentages. (female; 53% and male 47%), the ages were represented in similar percentages: 3 years (31.3%), 4 years (39.3) and 5 years (29.4). Regarding the level of dental caries: 52.8% of the sample had a very high ceo-d; followed by high with 23.9%; moderate with 14.1% and low with 9.2%; According to weight for height, 74.8% had a normal weight for height; 10.4% were obese; 9.2% were overweight and 5.5% were malnourished; According to size for age, 86.5% had a size for normal weight; 11.7% were sick; 1.8% were discharged; According to weight for age, 74.8% had a normal weight for height; 10.4% were obese; 8.6% were overweight and 6.1% were malnourished. The average age was 3.98 years. The average number of brushing times per day was 2.10. The average number of decayed teeth was 4.69 per patient. The average number of teeth extracted was 0.45. The average number of teeth filled was 1.38. CONCLUSION: There is no relationship between ceo-d and nutritional status (p=0.962). But if there is a relationship between the weight and height of the sample (p=0.002); However, there is no relationship between ceo-d and sex (p=0.254). Likewise, there is no relationship between ceo-d and the variables: weight for height (p=0.909); height for age (p=0.203); weight for age (p=0.962). However, a relationship was found between ceo-d and the number of brushing times per day (p=0.000); determining the relationship in decayed, extracted and filled teeth. Demonstrating that 89.6% of the sample says they brush twice a day.